Dynamic channel selection for meshed wireless personal area network - Abdul Lateef, Ahmed (2015)
Wireless Personal Area Network refers to the interconnection among devices within a limited range of meters. The need to extend the coverage area of the WPAN without increasing the transmission power and response to the suddenly user increase in the network is one of the primary motivations that lead researchers to investigate the required changes for topology and study performance parameters to support the meshed WPAN. Therefore, many prototypes have emerged as a draft candidate, but many problems have arisen. One of these problems is the restricted capacity of the meshed WPAN since they use TDMA scheme. This thesis focused on the meshed WPAN to investigate and determine the possibility of exploiting the available increasing in wireless nodes to enhance the performance and increase the capacity for meshed WPAN. A Dynamic Channel Selection Algorithm has been suggested. This algorithm uses the available channels, which are five channels in the WPAN, to enable simultaneous transmission of two or more channels to achieve a high packet delivery ratio and better performance of the network especially when it uses applications that needs high traffic. Furthermore, it gives the network the flexibility to increase the capacity when new devices want to join the network by allocating their location in the working topology. The new prototype of 46 wireless nodes was created by expanding an old prototype of 9 wireless nodes. The NS2 software tools function is used to implement the nodes in the network in order to examine the performance of the two prototypes network by making comparison.